2009
DOI: 10.1515/cclm.2009.044
|View full text |Cite
|
Sign up to set email alerts
|

A pilot survey of the use and implementation of cardiac markers in acute coronary syndrome and heart failure across Europe The CARdiac MArker Guideline Uptake in Europe (CARMAGUE) study

Abstract: Background: Guidelines on preferred cardiac marker strategies for investigation of patients with acute coronary syndromes (ACS) are available from the laboratory medicine and cardiology communities. Therefore, implementation of these guidelines into daily clinical practice should be a joint effort of laboratory specialists and clinicians. This was investigated in this survey. Methods: A pilot study was performed sponsored by the European Federation of Clinical Chemistry and Laboratory Medicine. A link to an on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 33 publications
(32 reference statements)
1
21
0
1
Order By: Relevance
“…Despite the recommendations of these groups, we found that a minority of hospitals currently use a cTn‐only strategy, although the proportion has increased substantially. Our data are consistent with the findings from the CARMAGUE study, which surveyed 300 European hospitals and reported that 31% of laboratories used cTn as the sole marker for diagnosis of AMI 13. Thus, there appears to be a world‐wide issue with adaptation of recommended guidelines for use of cTn that may have an important impact on public health.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Despite the recommendations of these groups, we found that a minority of hospitals currently use a cTn‐only strategy, although the proportion has increased substantially. Our data are consistent with the findings from the CARMAGUE study, which surveyed 300 European hospitals and reported that 31% of laboratories used cTn as the sole marker for diagnosis of AMI 13. Thus, there appears to be a world‐wide issue with adaptation of recommended guidelines for use of cTn that may have an important impact on public health.…”
Section: Discussionsupporting
confidence: 89%
“…We found wide variation in the choice of diagnostic cut points by institution, with cumulatively less than half (49%) using the 99th percentile, although use did increase over time. Others have also found a wide variation in decision cut‐point values for cTn despite recommendations to use the 99th percentile for diagnosis 13, 19. Although not a recommended practice, we found a significant proportion of hospitals (49%) still using 2 decision points to define an indeterminate troponin range 3.…”
Section: Discussionmentioning
confidence: 50%
“…The vast majority of cTn assays lack adequate precision at the 99th percentile value, and most assays cannot truly define this value for a normal reference population. Thus, inconsistency of analytical definition of a positive cTn result and MI diagnosis has been observed between assays when concentrations are near the 99th percentile values (2 ). Previously, undetectable cTn concentrations have been documented to contain substantial diagnostic and prognostic information (3)(4)(5)(6)(7)(8).…”
Section: © 2009 American Association For Clinical Chemistrymentioning
confidence: 99%
“…Prior studies evaluating the role of troponins in sepsis and septic shock were limited by the use of different troponin assays, small sample sizes, variations in definitions of elevated troponin levels, and loss of patients to follow‐up 2. These studies display marked heterogeneity because of lack of uniform adaptation of the 99th percentile of the upper reference limit as the standardized cutoffs 14. Thus, the epidemiology and prognostic value of troponin levels in patients with sepsis depend not only on the assay used but also on the cutoff values used.…”
Section: Introductionmentioning
confidence: 99%